High Performance Work Systems (Hpws) and Employee Satisfaction - Damaro Olusoji Arubayi (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The study examined the influence of a high-performance work system on employee satisfaction. The study mainly covered three selected companies in Delta State: Hallmark Business Solutions, Kleekit and Unicus. Four research questions were posed, from which the study objectives and hypotheses were derived. The cross-sectional research design was adopted for the study. The structured questionnaire was used as the main instrument of data collection while Yamane's formula was used to determine the sample size and the simple random sampling technique was utilized for selecting the samples from the population and simple percentage, frequency distribution table, mean and Pearson product-moment correlation statistical techniques were used to analyze the generated data. Findings showed that there is no significant relationship between selective hiring and employee satisfaction and there is no significant relationship between high results-based competition and employee satisfaction. The study further found that there is a significant relationship between training by the commitment and employee satisfaction and that there is a significant relationship between sharing key information and employee satisfaction. Following the findings, the study recommends that every organization should provide relevant training to its employees over time as this will enables employees to acquire needed skills and capabilities that enhance their confidence and level of satisfaction in an organization. The study also recommends that the management of every organization should provide compensation to employees based on exceptional or significant performance and organizations should eliminate or minimize the element of selective hiring from their high-performance work system. Finally, the study recommends that efforts should be made by organizations to boost employee satisfaction through modern mechanisms of employee-focused administration and management.